2017
DOI: 10.5455/njppp.2017.7.0518906062017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic ingestion of Bisphenol A on gut contractility in rats

Abstract: Background: Bisphenol A (BPA) is a plastic toxin widely used in manufacturing of plastic containers. It is known to produce a variety of toxic effects on body functions including reproduction, metabolism, and development. Despite the fact that the gastrointestinal tract is chronically exposed to food containing BPA, its effect on the gut motility is poorly understood. Aims and Objectives: The present study attempted to assess the small and large gut contractility in vitro in male rats fed with BPA-mixed food f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
(20 reference statements)
1
6
0
Order By: Relevance
“…In this study, animals given the low and high oral doses of BPS exhibited the same gastric changes as those reported by Dixit et al 20 These researchers found that BPS inhibited Ach‐induced contractions of the intestine and stomach. Further, Sharma and Madal 21 demonstrated the same previous finding by exposure to cumulative bath concentrations of BPA (0.1–100 μM) and BPS (0.1–100 μM), and this coincides with reduced serum gastrin levels in rats exposed to BPS in our study, with the long contact time between BPS and the gastric wall explaining the gastric changes.…”
Section: Discussionsupporting
confidence: 87%
“…In this study, animals given the low and high oral doses of BPS exhibited the same gastric changes as those reported by Dixit et al 20 These researchers found that BPS inhibited Ach‐induced contractions of the intestine and stomach. Further, Sharma and Madal 21 demonstrated the same previous finding by exposure to cumulative bath concentrations of BPA (0.1–100 μM) and BPS (0.1–100 μM), and this coincides with reduced serum gastrin levels in rats exposed to BPS in our study, with the long contact time between BPS and the gastric wall explaining the gastric changes.…”
Section: Discussionsupporting
confidence: 87%
“…The relaxative effect of BPA was also observed in studies using smooth muscle collected from other tissues. It was shown that BPA inhibited the contractile activity of the duodenum ( 37 ) and the distal ileum and mid colon in rats ( 8 ). This means that regardless of the origin of the smooth muscle origin it acts upon, BPA always has a relaxative effect.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, chronic ingestion high-concentration BPA (25 times the concentration used in the present study) decreased rat ileal contractions. [10] On reproductive system, BPA exerts toxic effect on uterine endometrial proliferation, uterine receptivity associated with implantation failure in animals. [6] In human beings, BPA exposure is associated with adverse birth outcome, sexual dysfunction, and impaired implantation.…”
Section: Discussionmentioning
confidence: 99%